Effect of IT Knowledge and IT Regulations on External Auditors' Performance: The Moderating Role of Audit Firm Size in Yemen - Al-Ansi, Ali Ali; Senan, Nabil Ahmad Mareai; Faaeq, Munadil Khaleel; Al-Swidi, Abdullah Kaid; Homaid, Abdo Ali; Al-Matari, Yahya Ali (2011)
The study aimed to investigate combined effect of IT knowledge, IT regulations of professional bodies, and audit firm size on auditors' performance in Yemen.Furthermore, this study tests the moderating role of firm size in the relationship between IT knowledge and auditors' performance.To examine the hypothesized model, the quantitative research design was employed. A questionnaire survey was used to collect the data from 274 external auditors working in Big-four firms, non-Big-four international firms, local firms and sole practitioners working in Yemen. To test the proposed hypotheses, the Partial Least Squares, Structural Equations Modeling Approach was employed.The model with direct effects and moderating effect achieves an appropriate level of predictive validity for the key endogenous construct (auditors' performance).In addition, the findings of the statistical results confirmed the significant effect of the IT knowledge, regulations of professional bodies, and firm size on external auditors' performance. The value of this paper was in showing the importance of IT knowledge of the auditors, IT regulations of the professional bodies, and firm size to enhance the overall external auditors' performance. More importantly, this paper reveal the significant role of firm size as moderating between the relationship of IT knowledge and auditors' performance.